Evaluasi Pasca Huni Studio Gambar Program Studi Arsitektur Fakultas Teknik UNLAM - Anna Oktaviana; Dahliani Dahliani; Prima Widya Wastuty (INFO-TEKNIK, 2005)
Drawing studio at Program Study of Architecture of UNLAM at this moment was felt unsupported the studying process if evaluated from the available space concerning the moving space requirement, equipment of support facility ( for example the drawing desk, desk, locker, etc.), the furniture arrangement situation regarding the human being movement circulation. This study conducted in order to get a good drawing studio condition evaluated from equipment of furniture facility, moving space requirement and the furniture arrangement situation move and location arrange the furniture situation to amenity the circulation movement of people.Data analysing will be using comparison method and rule about equipment of furniture facility, the furniture arrangement and space between furniture in the standard regulation become the reference to be compared to existing condition. Data obtained by this study was the form of qualitative data and quantitative data will be analysed qualitative in the form of studio layout drawing.Base to the conducted study hence obtained the conclusion that equipment of furniture facility was lack in number, the existing furniture arrangement of drawing studio at this moment did not support the good atmosphere needed, and existing moving space available for circulation in this time did not reach the standard regulation requirement. Overall evaluation concerning the equipment of furniture facility, the furniture arrangement, and standard moving space circulation compared to the existing moving space, and also number of student, hence obtained the conclusion that wide of drawing studio at this moment cannot served the comfortable activity needed.